Effects of Workforce, Tax Revenue, Unemployment, and Technological Advancement on Indonesia's Economic Development - Fanny Septya; John Atsu Agbolosoo; Astried Priscilla Cordanis; Mimi Nurfitasari; Novyandra Ilham Bahtera (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Inflation and unemployment are trade-offs for economic growth, and prolonged unemployment lowers GDP. With a GDP growth of 5.05% in 2023, Indonesia showed its resilience and strategic adaptability in the face of global economic uncertainty. This research examined factors influencing Indonesia's economic growth using macroeconomic indicators and time series data from 1974 to 2023. Stationarity tests (ADF and PP unit roots) and Johansen's cointegration confirmed long-term relationships among eight variables. The ARDL model investigated short and long-term dynamics, including CUSUM/CUSUMQ plots, SMPAE, and U-Theil inequality to assess causal relationships and model stability. ARDL results revealed that labor force participation, tax revenue, trade openness, urban population, unemployment, and technological advancement significantly impacted Indonesia's economic growth. Tax revenue, trade openness, foreign direct investment, and technological advancement positively influenced short-term growth. Short-run dynamics showed immediate economic adjustments affecting macroeconomic indicators and growth. The research determined that labor force participation, tax revenue, trade openness, urbanization, unemployment, foreign direct investments, and technological advancement were crucial for Indonesia's economic growth. The study suggests allocating resources to training, education, and skill development programs to boost workforce efficiency. The government should promote domestic production of tradable commodities, employ strategic tariffs and subsidies, and promote competitive sectors. The administration should nurture innovation, enhance access to technology, and invest in education. The government should improve tax collection, expand the tax base, and direct revenue toward growth-stimulating projects. Studi about interaction on macroeconomic indicators supporting agriculture development strategy.